Global survival trends for brain tumors, by histology: analysis of individual records for 556, 237 adults diagnosed in 59 countries during 2000–2014 (CONCORD-3). Issue 3 (10th November 2022) - Girardi, Fabio; Matz, Melissa; Stiller, Charles; You, Hui; Marcos Gragera, Rafael; Valkov, Mikhail Y; Bulliard, Jean-Luc; De, Prithwish; Morrison, David; Wanner, Miriam; O'Brian, David K; Saint-Jacques, Nathalie; et al.
Abstract: Background: Survival is a key metric of the effectiveness of a health system in managing cancer. We set out to provide a comprehensive examination of worldwide variation and trends in survival from brain tumors in adults, by histology. Methods: We analyzed individual data for adults (15–99 years) diagnosed with a brain tumor (ICD-O-3 topography code C71) during 2000–2014, regardless of tumor behavior. Data underwent a 3-phase quality control as part of CONCORD-3. We estimated net survival for 11 histology groups, using the unbiased nonparametric Pohar Perme estimator. Results: The study included 556, 237 adults. In 2010–2014, the global range in age-standardized 5-year net survival for the most common sub-types was broad: in the range 20%–38% for diffuse and anaplastic astrocytoma, from 4% to 17% for glioblastoma, and between 32% and 69% for oligodendroglioma. For patients with glioblastoma, the largest gains in survival occurred between 2000–2004 and 2005–2009. These improvements were more noticeable among adults diagnosed aged 40–70 years than among younger adults. Conclusions: To the best of our knowledge, this study provides the largest account to date of global trends in population-based survival for brain tumors by histology in adults. We have highlighted remarkable gains in 5-year survival from glioblastoma since 2005, providing large-scale empirical evidence on the uptake of chemoradiation at population level. Worldwide, survival improvements have been extensive, but some countries still lag behind. Our findings may help clinicians involved in national and international tumor pathway boards to promote initiatives aimed at more extensive implementation of clinical guidelines.